Operation peculiarities of airplane brake systems - Докучаев, В. Г.; Скрипка, В. Ф. (Proceedings of National Aviation University (archive), 1999)
Analyzed is the loading of airplane brake systems. Complex methods are proposed for investigation of highly loaded brake systems. The results of investigation of the influence of various factors on technical condition of friction units are given